Lipid peroxidation in plasma of rats treated with Fe-NTA: protective effect of the phenolic fraction of extra virgin olive oil - Deiana, M.; Rosa, A.; Corona, G.; Atzeri, A.; Incani, A.; Loru, D.; Melis, M. P.; Visioli, F.; Dessì, M. A. (Progress in Nutrition, 2007)
It has been reported that the phenolic fraction (PF) of extra virgin olive oil contains compounds that are important inhibitors of lipid peroxidation in vitro and are believed to be effective through their free radical scavenging and metal chelating properties. An excellent model of in vivo free radical induced damage, associated with extensive lipid peroxidation, is the ferricnitrilotriacetate (Fe-NTA) model. Intraperitoneal injection (i.p.) of Fe-NTA leads in rats to increasing oxidative stress, that starts from the plasma compartment, where Fe-NTA finds the ideal environment to react with oxidizable lipids, as unsaturated fatty acids (UFA) and cholesterol in lipoproteins particles. To investigate the action of the PF as inhibitor of the lipid peroxidation process in the plasma compartment, we treated Wistar rats with the PF (25 mg-50 mg/Kg bw) prior to the administration of a sub-lethal dose (15 mg Fe/Kg bw) of Fe-NTA. Fe-NTA treatment induced a significant decrease of UFA and cholesterol, together with an increase of fatty acids hydroperoxides (HP) and 7-ketocholesterol (7-keto). I.p. administration of PF significantly inhibited fatty acids and cholesterol oxidation, and reduced the levels of HP and 7-keto. Phenolic compounds may associate with lipoproteins particles, increasing their resistance against oxidation or may directly trap radicals generated in the plasma aqueous compartment.